2012
DOI: 10.1002/psc.2406
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the color formation by gradient temperature‐elevating Maillard reaction of soybean peptide‐xylose system based on interaction of l‐cysteine and Amadori compounds

Abstract: Light color and savory flavor enhancer are attractive for consumers and food producers. The effect of addition time of l‐cysteine on inhibiting color formation was investigated in soybean peptide‐xylose system, and the possible pathway was explored. Once dicarbonyl compounds were formed during the Maillard reaction, the addition of l‐cysteine had no color‐inhibiting effect; if l‐cysteine was added immediately after the Amadori compound was formed, the extraordinary color‐inhibiting effect was observed. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
8
31
0
Order By: Relevance
“…Results show that A 420 of samples with Cys first decreased and reached the lowest at 150 min, and then significantly increased but A 420 of blank samples increased gradually. These results are in good agreement with the previous findings (Cui et al., ; Huang et al., ; Yang et al., ). According to Huang et al.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Results show that A 420 of samples with Cys first decreased and reached the lowest at 150 min, and then significantly increased but A 420 of blank samples increased gradually. These results are in good agreement with the previous findings (Cui et al., ; Huang et al., ; Yang et al., ). According to Huang et al.…”
Section: Resultssupporting
confidence: 94%
“…Results show that A 420 of samples with Cys first decreased and reached the lowest at 150 min, and then significantly increased but A 420 of blank samples increased gradually. These results are in good agreement with the previous findings Huang et al, 2012;Yang et al, 2017). According to Huang et al (2012), the cysteine could react with MRIs and produce light-colored compounds so as to inhibit the intermediates to continue Maillard reaction.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the interaction between amadori compounds and cysteine in soybean-xylose Maillard reaction system, a novel gradient temperature-elevating Maillard reaction was developed for effective production of light-colored MRPs (Huang et al 2012). It has been generally accepted that antioxidant activity of MRPs are related to the brown compounds content, therefore it is quite necessary to evaluate the antioxidant activities of these lightcolored MRPs as well as flavor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The Cys content decreased by 13.40% during the first 5 days of post-fermentation, which is the smallest decrease observed among the amino acids and does not agree with various reports of high Cys losses. The study of Huang et al [30] revealed that Cys inhibits melanogenesis in the MR, and that its major role in the Amadori product, which is formed by the condensation and rearrangement of amino compounds and reducing sugars interfering with peptides and sugar Amadori formation, is to effectively preventing Amadori compounds from further forming deoxy-reductones and cyclization, inhibiting the generation of color substances. During the first 5 days post-fermentation, melanin is generated rapidly and Cys may not be very involved in inhibiting the MR during this stage.…”
Section: Hydrophilicity Analysis Of Hydrolysates During the Rapid Melmentioning
confidence: 99%